2001 Proceedings. 51st Electronic Components and Technology Conference (Cat. No.01CH37220)
DOI: 10.1109/ectc.2001.927681
|View full text |Cite
|
Sign up to set email alerts
|

Development of low-cost and highly reliable wafer process package

Abstract: A wafer level chip-scale-package (WLCSP) is expected to reduce the manufacturing cost of CSPs, but reliability of a solder joint for a large chip size of about 100 mm 2 without underfill assembly is still in question. To meet this needs, we have developed a highly reliable and low-cost WLCSP named wafer process package phase 2 (WPP-2). The package includes a built-in stress-relaxation layer for reducing the strain of the solder bumps. To lower the manufacturing cost of the package, the stress-relaxation layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, another fracture mode with a ductile fracture through the solder ball was also found. This fracture mode, usually seen in previous WLCSP structures [5], [7], [8] was not the desired mode for the SJP-WLCSP since it went against our design concept of releasing the stress caused from the CTE mismatch between silicon chip and FR-4 board. However, only one kind of fracture mode was found in the SiLK-wafer samples.…”
Section: Structurementioning
confidence: 93%
See 2 more Smart Citations
“…However, another fracture mode with a ductile fracture through the solder ball was also found. This fracture mode, usually seen in previous WLCSP structures [5], [7], [8] was not the desired mode for the SJP-WLCSP since it went against our design concept of releasing the stress caused from the CTE mismatch between silicon chip and FR-4 board. However, only one kind of fracture mode was found in the SiLK-wafer samples.…”
Section: Structurementioning
confidence: 93%
“…After the delamination layer was formed, photopatternable polyimide material used as the bottom insulating layer (BIL) for the metal redistribution traces was spin coated on the wafer and defined. The thickness of the bottom insulating layer was about 5 . The next step was a Ti/Cu/Ni/Au redistribution layer (RDL) formed by Ti/Cu sputtering, Ni electroplating followed by immersion in Au.…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement of solder joint reliability also studied by placing large dummy balls at the outermost corners of the solder joint array [12]. Kazama et al [13] employed the finite element analysis (FEA) to optimize the built-in stressrelaxation layer for reducing the strain of the solder bumps. Gao et al [14] reported a novel design to enhance the board level reliability by incorporating a compliant polymer layer under the UBM.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the MCM could be developed at lower cost and in a quicker turnaround time (QTAT) than a SOC, because existing chips were used in its manufacture. The two chips i n the MCM are wafer process packages (WPPs) [1] [2]. Figure 2 shows the crosssectional structure of the WPP.…”
Section: Introductionmentioning
confidence: 99%